2008
DOI: 10.1128/aac.01342-07
|View full text |Cite
|
Sign up to set email alerts
|

The Antimicrobial Peptide NK-2, the Core Region of Mammalian NK-Lysin, Kills Intraerythrocytic Plasmodium falciparum

Abstract: In a time of dramatically increasing resistance of microbes to all kinds of antibiotics, natural antimicrobial peptides and synthetic analogs thereof have emerged as compounds with potentially significant therapeutical applications against human pathogens. Only very few of these peptide antibiotics have been tested against protozoan pathogens that are a major cause of morbidity and mortality in large parts of the world. Here, we studied the effect of NK-2, a peptide representing the cationic core region of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
39
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(42 citation statements)
references
References 45 publications
3
39
0
Order By: Relevance
“…The less potent of these are hemolytic at their active concentrations, although erythrocytes infected with P. falciparum appear often to be more susceptible to lysis than noninfected host cells (56 -58). More potent peptides, including acylated derivatives (58,59) and, in particular, peptide analogues (60), are active at concentrations far below that required for erythrocyte lysis, and such peptides have been shown to be localized at the parasite membrane within infected erythrocytes (56,59). In the present study, the antiplasmodial activity of, in particular, D-HALO-rev indicates that histidinerich peptides can be designed that can also enter P. falciparuminfected erythrocytes at sublytic concentrations and kill the parasite.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The less potent of these are hemolytic at their active concentrations, although erythrocytes infected with P. falciparum appear often to be more susceptible to lysis than noninfected host cells (56 -58). More potent peptides, including acylated derivatives (58,59) and, in particular, peptide analogues (60), are active at concentrations far below that required for erythrocyte lysis, and such peptides have been shown to be localized at the parasite membrane within infected erythrocytes (56,59). In the present study, the antiplasmodial activity of, in particular, D-HALO-rev indicates that histidinerich peptides can be designed that can also enter P. falciparuminfected erythrocytes at sublytic concentrations and kill the parasite.…”
Section: Discussionmentioning
confidence: 99%
“…One major difference is that Plasmodium plasma membranes also have an extremely low cholesterol content (61). Furthermore, both exposure of phosphatidylserine at the external surface of the erythrocyte plasma membrane (40,56) and increased membrane fluidity and disorder, accompanying an increase in the proportion of unsaturated lipid acyl chains in the erythrocyte membrane phospholipids and a slight reduction of the cholesterol content (62)(63)(64)(65), have been demonstrated postinfection. In contrast, healthy erythrocyte membranes retain asymmetry, and phosphatidylserine is not presented at the external surface prior to a pathological stimulus (40).…”
Section: Discussionmentioning
confidence: 99%
“…NK-2 is a peptide representing the cationic core region of the lymphocytic effector protein NK-lysin, which is found in NK cells and cytotoxic T cells (13). NK-2 has been found active against Gram-positive and Gram-negative bacteria, parasitic protozoa such as Trypanosoma cruzi (14) and Plasmodium falciparum (13) and the fungal pathogen Candida albicans (15). LL-37, an amphipathic ␣-helical peptide, is expressed in neutrophils, macrophages, monocytes, myeloid bone marrow cells, and epithelial cells.…”
mentioning
confidence: 99%
“…In addition, the results also showed that haemolysis of parasitised RBCs was negligible even after 48 h of incubation with peptide in combination with CQ. Literature shows that there are a number of natural and engineered AMPs with antiplasmodial activity, such as cecropin, magainin, defensin, gomesin, lipodermaseptin derivatives and defensin derivative NK-2 [29,30]. However, most of them fall short of the requirements for an effective antiplasmodial molecule, primarily because they lose their effectiveness in the presence of serum proteins and simultaneously cause high haemolysis.…”
Section: Discussionmentioning
confidence: 99%